Soil fertility management in Babati: A practical guide on good agricultural management practices in smallholder farming systems - Kihara, Job Maguta; Kinyua, Michael; Massawe, Prosper; Kyekaka, Jetrida (2022)
Working with farmers and extension staff within the Ministry of Agriculture and interactions with a broad range of researchers across national research and CGIAR Centers operating in Northern Tanzania resulted in a wealth of experience and knowledge that we bring forward in this guide. We have observed wide yield gaps across farms and experienced first-hand key challenges faced by farmers as we worked in their fields, interacted in field days, participatory technology evaluations, exchange visits and brainstorming meetings with farmers. High attainable yields observed by some individual farmers and researchers in experimental and demonstration trials clearly show potential of applying simple agronomic and other supporting practices to change fortunes of farmers. This is what inspired this guide.